2022
DOI: 10.1155/2022/5396628
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of Exosomes Derived from Trained Natural Killer Cells versus Non‐Trained One: More Functional and Antitumor Activity

Abstract: Background. Natural killer (NK) cells are cytotoxic lymphocytes of the innate immune system, capable of killing viral-infected and cancerous cells. NK cell-mediated immunotherapy has remarkably changed the current paradigm of cancer treatment in recent years. It emerged as a safe and effective therapeutic approach for patients with advanced-stage leukemia. Several immune-escape mechanisms can be enacted by cancer cells to avoid NK-mediated killing. Exosomes released by NK cells that carry proteins and miRNAs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…As an important part of innate immune responses, exosomes secreted by NK not only carry the characteristic markers of exosomes, but also the markers of NK, such as NKG2D, perforin, granzyme, and CD40L ( Federici et al, 2020 ). Some studies have found that exosomes extracted from NK after co-culture with K562 cells can upregulate the expression of caspase three and p53 genes in tumor cells apoptotic signaling pathway to exert anti-tumor activity and exert rapid cytotoxic activity on target cells, which is more effective than intact NK ( Mohammadi et al, 2022 ). T lymphocytes can include CD4 + T cells and CD8 + T cells because of the different CD molecules they express.…”
Section: Exosomes As Tumor Immunomodulatory Moleculesmentioning
confidence: 99%
“…As an important part of innate immune responses, exosomes secreted by NK not only carry the characteristic markers of exosomes, but also the markers of NK, such as NKG2D, perforin, granzyme, and CD40L ( Federici et al, 2020 ). Some studies have found that exosomes extracted from NK after co-culture with K562 cells can upregulate the expression of caspase three and p53 genes in tumor cells apoptotic signaling pathway to exert anti-tumor activity and exert rapid cytotoxic activity on target cells, which is more effective than intact NK ( Mohammadi et al, 2022 ). T lymphocytes can include CD4 + T cells and CD8 + T cells because of the different CD molecules they express.…”
Section: Exosomes As Tumor Immunomodulatory Moleculesmentioning
confidence: 99%
“…This orchestrated response is notably accompanied by a marked increase in the production of NK-EVs ( 47 ). Furthermore, EVs produced by memory-like NK cells exhibit greater toxicity towards cancer cells ( 48 ).…”
Section: Basic Biology Of Nk Cell-derived Extracellular Vesiclesmentioning
confidence: 99%
“…EVs derived from NK cells previously exposed to neuroblastoma cells (NB), which express NCRs and activation signals, can activate resting human NK cells, enhancing their NK-mediated anti-NB tumor response ( 49 ). NK cells exposed in advance to EVs derived from CML cells exhibit higher gene expression levels of caspase 3 and P53 compared to the untreated EVs group, showing stronger cytotoxic effects on tumor cells ( 48 ).…”
Section: Basic Biology Of Nk Cell-derived Extracellular Vesiclesmentioning
confidence: 99%
“…[13] Because NK vesicles express typical surface markers and contain similar biological components as parental NK cells, active vesicles released from NK cells can induce apoptosis in tumor cells and have therefore been developed as promising anticancer agents. [14][15][16] Despite their therapeutic potential, the clinical application of EVs has been hindered by their low productivity and an incomplete understanding of their functional mechanisms. To overcome these limitations of EVs, we artificially induced EVmimicking vesicles on NK cells by chemical treatment and mechanical stimulation.…”
Section: Introductionmentioning
confidence: 99%